From roaring on the hilltop to weeping by the bedside: protector personas of fathers raising children with autism spectrum disorder. (7th July 2016) - Lashewicz, Bonnie; Cheuk, Samantha; Shave, Kassi
Abstract : While an extensive body of work exists to support our understanding of the experiences of contemporary mothers, far less attention has been paid to the experiences of contemporary fathers. In this article, we set our sights on fathers; specifically, we examine how fathers strategically present their identities, or 'personas', as protectors, in relation to raising children with autism spectrum disorder (ASD). ASD is the most common neurological disorder affecting children in Canada and the communication and behavioural challenges associated with a child's ASD diagnosis make for relatively intense parenting experiences. We tap into this intensity to examine how 28 fathers of children with ASD define and present themselves relative to the developmental needs of their children. The fathers exemplify an impactful blend of traditional and modern father ideals through personas that entail tender involvement along with fierce protectiveness.